Successfully Integrating Research into Plastic Surgery Training Programs. Issue 8 (November 2015) - Ballard, Tiffany N.S.; Sando, Ian C.; Kasten, Steven J.; Cederna, Paul S.
Abstract : Abstract: Successful integration of research into the educational mission of a plastic surgery residency program requires the support and dedication of the faculty members to create a culture that promotes innovation, discovery, and advancement of the field of plastic surgery. Dedicated research time during plastic surgery training is beneficial to both the resident and training program. Regardless of whether residents plan to pursue an academic career or enter private practice, participating in research provides an opportunity to develop skills to think critically and mature professionally. In this article, we review the benefits of resident research to both the trainee and training program and discuss strategies to overcome barriers to integrating research into the curriculum.